Influence Game Zig-Zag Run To Skills Motoric Rough Children Aged 5-6 Years - Shalih Diva Azizah; Rusmayadi Rusmayadi; Herman Herman (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
The gross motor skills of children in the control group before and after being given a ball relay game, knowing the description of the gross motor skills of children in the experimental group before and after being given a zig-zag run game, and analyzing the effect of the zig-zag run game on the gross motor skills of children aged 5-6 years at Aisyiyah Bustanul Athfal Parangtambung Makassar Kindergarten. This study uses a quantitative approach with a quasi-experimental research type and a Nonequivalent Control Group Design. The research sample consisted of 20 children divided into two groups, namely 10 children in the experimental group and 10 children in the control group. The data collection technique was carried out through observation using a gross motor skills assessment sheet which includes locomotor, non-locomotor, and manipulative aspects. The data were analyzed using descriptive statistics and inferential statistics through the Mann-Whitney test. The results showed that the gross motor skills of children in the control group increased after participating in the ball relay game, but the increase was still in the Less category. Meanwhile, the experimental group that received treatment in the form of a zig-zag run game showed a more optimal increase until most of the children were in the Very Good category. The results of the Mann Whitney test obtained an Asymp. Sig. (2-Tailed) value of 0.000 (<0.05), which indicated a significant difference between the experimental group and the control group. Thus, it can be concluded that the zig-zag run game has a significant effect on improving the gross motor skills of children aged 5-6 years at Aisyiyah Bustanul Athfal Parangtambung Kindergarten, Makassar.